2010
DOI: 10.1016/j.eeh.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The upswing of regional income inequality in Spain (1860–1930)

Abstract: a b s t r a c tThis paper studies the evolution of Spanish regional inequality from 1860 to 1930. The results point to the coexistence of two basic forces behind changes in regional economic inequality: industrial specialization and labor productivity differentials. The initial expan sion of industrialization, in a context of growing economic integration of regions, promoted the spatial concentration of manufacturing in certain regions, which also benefited from the greatest advances in terms of labor producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
89
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 39 publications
4
89
0
7
Order By: Relevance
“…As has been pointed out recently, the early stages of economic development in Spain took place alongside a strong increase in spatial inequality both as regards the location of industry across the territory (Paluzie et al 2004) and levels of GDP per capita for the Spanish regions (Rosés et al 2010). In the analysis of the causes of this increase in regional inequalities and its relation with the presence of agglomeration economies in the industrial sector, Martínez-Galarraga (2012) has shown that the marked industrial specialisation of a small number of Spanish provinces came about, among other factors, due to their market size in the presence of economies of scale that acted as an agglomeration force.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As has been pointed out recently, the early stages of economic development in Spain took place alongside a strong increase in spatial inequality both as regards the location of industry across the territory (Paluzie et al 2004) and levels of GDP per capita for the Spanish regions (Rosés et al 2010). In the analysis of the causes of this increase in regional inequalities and its relation with the presence of agglomeration economies in the industrial sector, Martínez-Galarraga (2012) has shown that the marked industrial specialisation of a small number of Spanish provinces came about, among other factors, due to their market size in the presence of economies of scale that acted as an agglomeration force.…”
Section: Introductionmentioning
confidence: 99%
“…First of all it involves an economy that, because it was still in the early stages of economic development, was characterised by the presence of high transport costs (Herranz 2007;Prados de la Escosura and Rosés 2009). Also, all Spain's regions are at income levels clearly below the thresholds that would mark a change of trend in the relationship between agglomeration and growth (Rosés et al 2010). Within the framework of the industrialisation processes typical of the countries of central and southern Europe, economic growth in Spain over this period was led by advances in the industrial sector, in which various papers have shown the presence of agglomeration economies (Betrán 1999;Tirado et al 2002;Martínez-Galarraga et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations